Search for supersymmetry in events with b jets and missing transverse momentum at the LHC - Chatrchyan, S.; Khachatryan, V.; Sirunyan, A. M.; Tumasyan, A.; Adam, W.; Bergauer, T.; Dragicevic, M.; Eroe, J.; Fabjan, C.; Friedl, M.; Fruehwirth, R.; Ghete, V. M.; et al. (Springer, 2011)
A search for supersymmetry is presented using a sample of events with b jets and missing transverse momentum. The search uses a data sample of proton-proton collisions at a centre-of-mass energy of 7TeV, corresponding to an integrated luminosity of 35 pb(-1), collected with the CMS detector. A total of 0.33(-0.33)(+0.43) (stat.) +/- 0.13 (syst.) events is predicted, using control samples in the data, to arise from standard model processes, and one event is observed in the data. Upper limits are set at the 95% confidence level on the cross sections of benchmark supersymmetric models.
Keywords: Hadron-Hadron Scattering